Digital Strategy in Enhancing Brand Equity of Pantai Matahari Tourism Sumenep - Ni'mah, Ana Tsalitsatun; Arif, Muchamad; Tahir, Muhlis; Diana, Luluk Mauli; Stefany, Evy Maya (Jurnal Ilmiah Pangabdhi, 2024)
This community service article delves into the implementation of a digital strategy aimed at elevating the brand equity of Pantai Matahari Tourism in Sumenep. Pantai Matahari, boasting natural beauty and cultural richness, holds significant potential as a tourist destination. However, its underdeveloped brand and limited exposure hinder the realization of its full tourism potential. Through an in-depth analysis of the tourism landscape in Sumenep, key elements for branding are identified. A meticulously crafted digital marketing strategy is then introduced to enhance the visibility and popularity of Pantai Matahari Tourism in the digital realm. This strategy incorporates social media and content marketing to engage a broader audience. The outcome of this initiative includes the establishment of a robust brand identity for Pantai Matahari Tourism, leading to increased public awareness and visitor interest. Collaborative efforts with local stakeholders and businesses further contribute to strengthened tourism infrastructure and attract new investments. The findings underscore the positive impact of tailored branding and digital marketing strategies on the development of Pantai Matahari Tourism, fostering economic benefits for local communities while preserving natural and cultural treasures. This community service initiative signifies a tangible contribution to sustainable tourism development in Sumenep.